Appointment as a Paper Reviewer for National Research and Innovation Conference for Graduate Students in Social Sciences 2014, UPM - Fatahyah, Yahya (Universiti Malaysia Sarawak, UNIMAS, 2014)
Dr Fatahyah Yahya was appointed as a paper reviewer for National Research and Innovation Conference for Graduate students in Social Sciences 2014 ( 5-7 December 2014), Faculty of Economics and Management ,UPM